Assessing adolescents' readiness for action and attitudes toward obesity prevention: Instrument development and psychometric properties. (2nd December 2022) - Grewal, Navnit Kaur; Klepp, Knut‐Inge; Banik, Anna; Bröer, Christian; Holbæk, Helene; Luszczynska, Aleksandra; Macauley, Talia; Rutter, Harry; Lien, Nanna
Summary: Engaging adolescents in obesity prevention is a main objective of the CO‐CREATE project. This paper presents the development of a questionnaire to assess readiness for action and attitudes toward obesity prevention among adolescents. The questionnaire was developed based on literature searches and internal discussions with experts in the CO‐CREATE consortium. The questionnaire was translated, back translated, and pretested for time and comprehensiveness by adolescents from five countries (the Netherlands, Norway, Poland, Portugal, and the United Kingdom). Exploratory factor analysis was performed, and internal reliability of the resulting factors was determined using baseline data from Poland and Norway. Furthermore, test–retest reliability was assessed in a sample of Norwegian adolescents. The exploratory factor analysis on readiness for action identified four factors. Analysis on attitudes toward obesity prevention identified four factors on responsibility and five factors on drivers of behavior. Six of the factors had a Cronbach's alpha value above 0.70, five factors had a value between 0.60–0.70, whereas the remaining two factors were below 0.60. The test–retest correlation ranged from 0.46 to 0.87. The exploratory factor analyzes on readiness for action identified the same factors as hypothesized in the development of the questionnaire, whereas attitudes toward obesity prevention identified more factors than initially assumed. The questionnaire is considered reliable as a tool for measuring adolescents' readiness for action and attitudes toward obesity prevention.